Mollaret meningitis: a case report - Pişkin, Ibrahim Etem; Yarimay, Güneş (The Turkish Journal of Pediatrics, 2010)
Mollaret meningitis is characterized by three or more episodes of benign recurrent aseptic meningitis in which symptoms and signs resolve spontaneously within two to five days. Severe headache with an acute onset, fever and meningismus are the main clinical features. We report a case of Mollaret meningitis in a seven-year-old girl who presented with four aseptic meningitis episodes in one year.